An efficient XOR-based visual cryptography scheme with lossless reconfigurable algorithms - Huan Wang; Zhongyuan Jiang; Qing Qian; Hong Wang (International Journal of Distributed Sensor Networks)
This article proposes an efficient XOR-based visual cryptography scheme with lossless reconfigurable algorithms, which includes an encryption and a decryption schemes for gray-scale and color secret images. The encryption scheme aims to encrypt secret images by mapping them to several shared images that do not suffer any pixel expansion problem and do not reveal any information of the secret images by considering a random column selection algorithm based on the 0-mapping and 1-mapping matrices, where the two matrices are dynamically generated in the encryption scheme. Moreover, the proposed decryption scheme can reconstruct the secret images with only a series of XOR operations. The reconstructed images do not suffer any contrast distortion and pixel expansion problems comparing with their original secret images. Finally, the proposed two schemes are illustrated with the practical examples.